Indigenous language publishing and national development: the yoruba language example (2007)
Language is a very unique human property and communication is one of its overriding goals. Communication enables man to interact with another, extend himself to others, expand his frontiers of knowledge and experience. Though the whole process of communication which can be at different levels is a complex one. mass communication is the most intricate as it is a mass mediated forum for reaching several people simultaneously. Each of the two subsets of mass communication — the print and electronic media has multifarious channels out of which publishing is notable. Publishing is indeed the horse on which meaningful development rides. Since a tree must be climbed from the bottom, indigenous language publishing occupies the root of meaningful education, which is the veritable sine qua non of both individual and national development. In this era of civil rule, it is the onus of the government and policy makers to reposition indigenous language publishing for mass mobilisation, social re-engineering and stable polity. This paper sets out to examine and relate the place of Yoruba language publications to national development in the Nigerian heterogenous society.